Perceived Neighborhood-level Drivers of Food Insecurity Among Aging Women in the United States (P04-155-19). (13th June 2019) - Shieh, Jacqueline; Weiser, Sheri; Whittle, Henry; Ofotokun, Ighovwerha; Adimora, Adaora; Tien, Phyllis; Leddy, Anna
Abstract: Objectives: Aging populations in the United States (US) exhibit high rates of both food insecurity and chronic illness. Few studies have explored in depth how food insecurity arises among such populations, and how it interacts with experiences of aging. We qualitatively explored how aging, low-income women experience food insecurity at multiple sites across the US, focusing on the neighborhood-level factors that influence these experiences. Methods: Study participants were drawn from the San Francisco, CA, Atlanta, GA, and Chapel Hill, NC sites of the Women's Interagency HIV Study (WIHS), a cohort study of women with or at risk for HIV. Using purposive sampling, we recruited 38 women who were food-insecure, 50 years of age or older, either with or at risk for HIV, and from different neighborhoods within each site. Semi-structured interviews explored participants' perceptions of how their neighborhood influenced their experiences with food security and aging. An inductive-deductive approach was used to thematically analyze the data. Results: Participants across the three sites explained that food insecurity was related to limited access to food stores. In San Francisco, this limited access primarily resulted from high food prices, whereas in Atlanta and Chapel Hill long distances to food stores and poor public transport systems were prominent. Most participants also described being dependent on food aid programs, but often found this difficult due to poor quality food and long wait times. Aging-related issues emerged as a cross-cutting theme. Both HIV + and HIV- women explained how fatigue, poor strength, and joint pains all amplified their barriers to accessing food. Women with chronic illness, regardless of HIV status, also found it difficult to afford healthy and nutritious food, which in turn further aggravated their poor health. Conclusions: Findings from this study suggest that older women across different settings in the US experience multiple barriers to navigating the food system, with key similarities and differences in barriers and systems of institutional support. While future programs should address common neighborhood-level barriers such as the availability and affordability of healthy foods and transportation, they should also be tailored to aging women, and to the unique local context. Funding Sources: NIAID.